2021
DOI: 10.1186/s42523-021-00096-2
|View full text |Cite
|
Sign up to set email alerts
|

Salmon gut microbiota correlates with disease infection status: potential for monitoring health in farmed animals

Abstract: Background Infectious diseases cause significant production losses in aquaculture every year. Since the gut microbiota plays an essential role in regulating the host immune system, health and physiology, altered gut microbiota compositions are often associated with a diseased status. However, few studies have examined the association between disease severity and degree of gut dysbiosis, especially when the gut is not the site of the primary infection. Moreover, there is a lack of knowledge on w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 98 publications
5
67
1
Order By: Relevance
“…Overall, the salmon gut mucosa was dominated by the genus Mycoplasma ( Fig. 1B ), a known commensal of the salmon intestinal microbiome ( 9 , 34 38 ). However, there was evidence that the gut microbiota differed between uninfected and infected individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the salmon gut mucosa was dominated by the genus Mycoplasma ( Fig. 1B ), a known commensal of the salmon intestinal microbiome ( 9 , 34 38 ). However, there was evidence that the gut microbiota differed between uninfected and infected individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, it has recently been suggested that Mycoplasma , due to its dominance in the distal intestine of rainbow trout and other farmed salmonids, could have a mutualistic relationship with its host ( Rasmussen et al, 2021 ). In Atlantic salmon ( Salmo salar ), the abundance of Mycoplasma has positively been associated with improved growth, carotenoid utilization, and disease resilience of the host ( Bozzi et al, 2021 ). In addition, this genus harbors genes for long-chain polymer degradation, such as chitin, which is particularly abundant in insects, that are part of the natural diet of juvenile salmonids.…”
Section: Discussionmentioning
confidence: 99%
“…The fish gut microbiome is essential to systemic function, fish health 44 , immune support 45 , and digestive capacity 46 . However, the factors that govern the microbial community colonisation, assembly, and succession in fish species are poorly understood, in terms of both the ecological assembly mechanisms and development within the life cycle.…”
Section: Discussionmentioning
confidence: 99%